1068 Cranial Fasciitis of the Temporal Bone. (12th October 2021) - Zuccarelli, A; Wright, B; Trimble, K
Abstract: We present the case of a child with a rare benign tumour of the temporal bone. A nine-month-old girl was referred to her local paediatric hospital with a painless right-sided, post-auricular swelling increasing in size in the preceding two months. On examination there was a 2x2cm mass overlying the temporal bone posterior to the right ear. The mass was firm, immobile, non-tender and well circumscribed. Ultrasound demonstrated a 1.9cm subcuticular mass with evidence of intracranial extension through the suture. Vascular flow and hyperechoic foci were demonstrated within the lesion. The local paediatric team requested magnetic resonance imaging (MRI) and computed tomography (CT) of temporal bone prior to referral to tertiary care centre. Imaging displayed a 2cm expansile lesion of the temporal bone with cortical loss and effacement of underlying dural venous sinus. The patient proceeded to incisional biopsy for tissue diagnosis which was suggestive of cranial fasciitis. Following discussion at the regional multidisciplinary meeting, she underwent surgical excision of the tumour in a joint Neurosurgery/Otology case. The tumour was fully resected macroscopically, with the normal surrounding bone and mastoid air cells preserved. Final histopathology showed a highly cellular lesion composed of spindle cells arranged in fascicles, with areas of myxoid background and confirmed the tumour to be cranial fasciitis. The child has made a good recovery and will be kept under close clinical follow-up. This case demonstrates a rare benign tumour of the temporal bone that may present to an otolaryngologist and the importance of tissue diagnosis, imaging and multidisciplinary management.